Penerapan Motion Graphic Dalam Video Sosialisasi Dampak Negatif Peredaran Rokok Ilegal - Gagad Seto Hanityo; Anthony Y.M. Tumimomor; Birmanti S. Utami (Besaung : Jurnal Seni Desain dan Budaya, 2025)
This study is based on the high rate of illegal cigarette distribution in Boyolali Regency, which has been increasing. The distribution of illegal cigarettes has the effect of causing losses to the state due to a decrease in excise revenue and has a negative impact on public health. The Boyolali Communication and Information Agency (Diskominfo) has made prior endeavors to raise awareness about the distribution of illegal cigarettes. However, the media used was deemed aesthetically unappealing in terms of both visuals and audio. Furthermore, there is a paucity in the dissemination of information regarding the adverse impacts of illegal cigarette distribution. The central objective of this study is to design an informational video that can effectively and persuasively convey information about the negative impacts of illegal cigarette distribution to the public. The research method utilized a qualitative approach with a linear design strategy, which encompassed five primary stages: The following five stages were identified: (1) problem identification, (2) data collection through interviews and literature review, (3) data analysis, (4) video design, which includes pre-production, production, and post-production stages, and (5) testing and drawing conclusions. The video was designed with a persuasive and educational approach, combining creative motion graphic visual elements with clear narration and language that is easily comprehensible to the general public. The final result of this research is a socialization video for the community to raise awareness of the dangers and impacts of illegal cigarettes and encourage behavioral change in the community to reject and stay away from illegal cigarettes.